The effect of smartphones and playing video games on decision-making in soccer players: A crossover and randomised study - Fortes, L. S.; De Lima-Junior, D.; Fiorese, L.; Nascimento-Júnior, J. R. A.; Mortatti, A. L.; Ferreira, M. E. C. (Journal of Sports Sciences, 2020)
The objective of this study was to analyse the effect of the use of social networks in smartphones or playing video games on the passing decision-making performance in professional soccer athletes. Participants were 25 male professional soccer athletes (mean ± SD: age 23.4 ± 2.8 years). The participants performed three randomised conditions divided into three groups: control (CON), smartphone (SMA), and video game (VID). Before and after each experimental condition, the Stroop Task assessed the level of induced mental fatigue. Then, the athletes performed a simulated soccer match. A CANON® camera recorded the matches for further analysis on passing decision-making performance. A group effect was identified (p < .01) with impairment on passing decision-making performance for the SMA (p = .01, ES = 0.5) and VID (p = .01, ES = 0.5) conditions. We concluded that the use of social networks on smartphones and/or playing video games right before official soccer matches might impair the passing decision-making performance in professional soccer athletes.